A comparison of three questionnaires to predict the risk of obstructive sleep apnea and hypopnea syndrome in adults - Escobar Baigorria, Ricardo Andres (2021)
Objective: To determine the differences in the prediction of the risk of developing obstructive sleep apnea–hypopnea syndrome (OSAHS) by comparing the results of the Berlin Questionnaire (BQ), the STOP-Bang (SB) Questionnaire and the Epworth Sleepiness Scale (ESS) in patients admitted to the Hospital Nacional Dos de Mayo from 2019 to 2020. Materials and methods: A quantitative, observational, descriptive, prospective and cross-sectional clinical study of diagnostic tests. A sample of 304 patients older than 18 years was included in the research. The results are presented with frequencies, measures of central tendency and dispersion. The variables were associated using the chi-square test. The sensitivity and specificity of the BQ and ESS were measured against the SB Questionnaire. A p value less than 0.05 was considered as statistically significant. Results: The average age of the study population was 52.89 ± 15.97 years and adults under 50 years of age (40.5 %) prevailed. Sixty point five percent (60.5 %) of the participants were males. The average BMI was 30.74 ± 6.02 kg/m2, with the overweight category being the most numerous (43.40 %). Forty-two point eight percent (42.8 %) of the participants had hypertension. According to the SB Questionnaire, BQ and ESS, 77.0 %, 62.5 % and 60.5 % had a high risk of developing OSAHS, respectively. The questionnaires showed an association between age, sex, nutritional diagnosis and arterial hypertension, and a high risk of developing OSAHS (p < 0.05). There is a weak correlation between the SB Questionnaire and BQ (Kappa: 0.39), and between the SB Questionnaire and ESS (Kappa: 0.33). Conclusions: The abovementioned questionnaires are useful tools to predict the risk of developing OSAHS. They show a significant but weak correlation between them. However, they should be considered as rapid and reliable screening tests.